2002
DOI: 10.1103/physrevlett.89.198102
|View full text |Cite
|
Sign up to set email alerts
|

Insulating Behavior ofλ-DNA on the Micron Scale

Abstract: We have investigated the electrical conductivity of λ-DNA using DNA covalently bonded to Au electrodes. Thiol-modified dTTP was incorporated into the 'sticky' ends of bacteriophage λ-DNA using DNA polymerase. Two-probe measurements on such molecules provide a hard lower bound for the resistivity ρ > 10 6 Ωcm at bias potentials up to 20 volts, in conflict with recent claims of moderate to high conductivity. By direct imaging, we show that the molecules are present after the measurements. We stress the importanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
157
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(171 citation statements)
references
References 21 publications
11
157
0
3
Order By: Relevance
“…These reports suggest this effect may be related to the behaviour of the interfacial layer and ion transport in monovalent electrolytic solutions in accelerating frames 24,25 . We have observed a significant contribution in the unloading configuration for STE buffer alone (Df ¼ À0.3260(29) Hz g À 1 , and DG nonlinear), which was subsequently 'screened' 26 by the presence of both oligos and lambda DNAs, making the effect negligible in the current set of experiments. Further investigation is required to explain this precisely.…”
Section: δF Loadingmentioning
confidence: 65%
“…These reports suggest this effect may be related to the behaviour of the interfacial layer and ion transport in monovalent electrolytic solutions in accelerating frames 24,25 . We have observed a significant contribution in the unloading configuration for STE buffer alone (Df ¼ À0.3260(29) Hz g À 1 , and DG nonlinear), which was subsequently 'screened' 26 by the presence of both oligos and lambda DNAs, making the effect negligible in the current set of experiments. Further investigation is required to explain this precisely.…”
Section: δF Loadingmentioning
confidence: 65%
“…At the time, we thought in terms of electron currents in DNA (Ratner, 1999;Porath et al, 2000) that could interact with the EM fields and lead to DNA chain separation. It is now questionable if these currents occur with any frequency, and whether they occur over a large enough number of bases to activate DNA during short exposures (Tran et al, 2000;Boon and Barton, 2002;Zhang et al, 2002).…”
mentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] Thus, the binding of DNA to the metallic leads could affect the electronic structure of the molecule itself. 25,26 Fortunately, in the DNA-metal junction case, one can restrict the analysis to the weak coupling limit, 12,27 and consider the following onedimensional effective Hamiltonian, 16…”
Section: Model Descriptionmentioning
confidence: 99%
“…12 Recent transport experiments have shown that chemical bonding between DNA and metal electrodes is a prerequisite for achieving reproducible conductivity results. 17,[20][21][22][23][24] In a previous work, we considered the role of contact effects in a polyGACT single strand connected to metallic leads at both ends. In general, interference effects between the DNA molecular bands and the electronic structure of the leads at the metal-DNA interface degrades the transmission, as expected.…”
Section: Contact Effectsmentioning
confidence: 99%